Uma análise processual da linguagem escrita na Síndrome de Down - Rabelo, Gabriela Regina Gonzaga (2018)
In Down Syndrome, the presence of an extra chromosome brings a big impact on the quality of life of the subject, compromising their development as a biopsychosocial being, making this development slower than the typical development. Therefore, it is necessary to reflect that the learning process of reading and writing happens in phases and stages that are particular to each person, being this one disabled or not. Thence, it is important to do studies that analyze the process of appropriation of the written language system, considering the period before the school stage, in which the child already develops primitive techniques capable of performing similar functions, in other words, skills and abilities that will facilitate the learning of formal writing, until a stage where the child becomes proficient in reading and writing. General objective: Analyze the development of the written language of a subject with Down syndrome in a socio-interactionist perspective. Methodology: Research qualitative, interventionist, exploratory and retrospective. The source is documentary, where we will analyze the written material of a young woman with SD from early childhood through the third year of elementary school. Because it is a research involving human beings, the study is carried out according to the recommendations of the Research Ethics Committee. Results: In preschool from 3 to 6 years, the child had a significant gain in oral language, which had repercussions on their learning in social context, at age six she evolved into writing her name on the basis of her teacher's writing. In the first year, Gabriella was able to broaden her knowledge of the alphabetical principle, knowing all the letters of the alphabet and learning how to manipulate letters in the formation of syllables, words and phrases. However, there was no adaptation of the content to Gabriella, since in the second half of the year they presented the irregularities of the language to the child. During this period, the mediators played a fundamental role, giving her the most diverse opportunities and incentives for her to overcome all the difficulties that arose along the way, seeking to consider the child's point of view, her cognitive and linguistic abilities. In the third year, mediation in the textual planning process assisted the child in the production of a better quality text, subsidizing important knowledge of how to carry out a later textual planning in an autonomous way. Conclusion: The insertion of Gabriella in the school, the speech therapy and the stimulation of the family and the educators, provided several quantitative / qualitative gains to its development in all the dimensions of the language and in the cognition. It is noteworthy that Gabriella was not passive in this process, when she came in contact with the resources available in her environment, as well as in the interaction with children and adults, she developed her cognitive abilities and perfected her language, appropriating the content that was her provided in interaction environments.